Comparison of the efficacy and safety of hydroxyethyl starch 130/0.4 and Ringer's lactate in children with grade III dengue hemorrhagic fever - Risky Vitria Prasetyo; Abdul Latief Azis; Soegeng Soegijanto (Paediatrica Indonesiana, 2009)
Background Theoretically hydroxyethyl starch (HES) will givemore rapid recovery from shock, including in dengue shocksyndrome (DSS) and currently gained popularity for its lessdeleterious effects on renal function and blood coagulation.Objectives To compare the efficacy and safety ofHES 130/0.4 andRinger's lactate (RL) for shock recovery in children with DSS.Methods A randomized controlled study was performed on 39children admitted with DSS at Dr. Soetomo Hospital, Surabaya,between March and May 2007. Children were grouped intograde III (n=25) and grade IV (n=14) dengue hemorrhagicfever (DHF) according to the WHO criteria. Within eachgroup, subjects were randomly assigned to receive initial fluidresuscitation with either HES 130/0.4 (n=9 in the DHF grade IIIgroup, 10 in the DHF grade IV) or RL (n= 16 in the DHF gradeIII group, 4 in the DHF grade IV). Clinical and laboratory datawere collected to determine improvements in shock recovery andadverse reactions.Results In both the grades III and IV DHF, HES 130/0.4significantly decreased hemoglobin and hematocrit levels. Clinicalimprovements in pulse pressure and pulse rate were seen aftertreatment with HES 130/0.4 although these were statisticallyinsignificant if compared to the RL group. No differences in fluidrequirement and recurrent shock episodes were noted betweenthe RL and HES groups. No adverse reactions were found duringthe study.Conclusion HES 130/0.4 administration is effective and safe inchildren with DSS.